The Continued Living Adaptability from Traditional Kampung to Multistory Housing - Prayitno, Budi (2005)
This paper is a basic study which examines an affordable flat housing in the Indonesian cities by both macro level and micro level, that is housing needs and market analysis, and the living style transformation of low-income inhabitants. Firstly, we describe the characteristics of low cost flat market through the examination about the house ownership, typology of rental house, the subsidy and its affordability, Secondly, we make sure of the probIerns of who intend to own houses through the survey of inhabitants of rental flats on kampung redevelopment areas. Based on these circumstances, we suggest that, when rental housing is implement target for low-income people in the Indoizesian large city planning, it is necessary to make an appropriate planning for bushess a d living space, not simply of f i g , and at the same time, to design the space and use in consideration of the continuity with traditional kampung living style.